Pharmacists’ perspectives on implementing pharmacist-managed anticoagulant clinics in Makkah Region Ministry of Health Hospitals: A qualitative study - Wassan L. Zarei; Sarah M. Khayyat (PLoS ONE, 2026)
Objectives This study aimed to identify the pharmacists’ perspectives on the barriers and facilitators to implementing pharmacist-managed anticoagulation clinics (PMACs) in Ministry of Health (MOH) hospitals in the Makkah Region, Saudi Arabia. Methods This study employed a qualitative, cross-sectional design. An interview guide was developed after a review of the literature and the adaptation of the Consolidated Framework for Implementation Research tool. Semi-structured interviews were conducted with licensed regular pharmacists, clinical pharmacists, and pharmaceutical care leaders who were working or had worked in MOH hospitals in the Makkah Region. Results A total of 11 participants were interviewed. The barriers to implementing PMACs predominantly related to professional and interprofessional barriers (e.g., lack of leader support and staff expertise, physician resistance), organizational and operational barriers (e.g., lack of resources), and patient-related barriers (e.g., poor commitment to follow-up). The main facilitators to implementing PMAC services were associated with improving workforce capacity and training, leadership and interprofessional support, organizational and patient support mechanisms, and infrastructure and digital resources. Conclusion The factors identified in this study can be used to develop potential strategic plans to improve existing PMAC services and extend their implementation across the country. Future research should aim to quantify the effectiveness of PMAC services on patients’ clinical/non-clinical outcomes. Positive findings could provide further evidence of the value of PMAC services, speed up their expansion, and ensure their sustainability.